Another biomineralising protostome with an msp130 gene and conservation of msp130 gene structure across Bilateria. Issue 3 (June 2015) - Szabó, Réka; Ferrier, David E.K.
SUMMARY Msp130 genes are known for their association with biomineralisation, principally in echinoderm skeletogenesis. Recently, msp130 genes were shown to exist more widely across the animal kingdom, including in molluscs, and a hypothesis was formed that the genes had arisen independently in the deuterostome and mollusc lineages via horizontal gene transfer, thus facilitating the evolution of biomineralisation in these distinct lineages (Ettensohn, 2014). Here we show that another biomineralising protostome, the polychaete Spirobranchus (formerly Pomatoceros) lamarcki also possesses an msp130 gene, and expresses it during a biomineralisation process. However, based on analysis of gene structure, we hypothesize that the protostome and deuterostome msp130 genes did not originate from independent horizontal gene transfers, but instead are descended from a gene already present in the bilaterian ancestor, with the gene being secondarily lost from several lineages.